2019
DOI: 10.1016/j.ccell.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Constitutive and Inducible Chemokines Enables T Cell Engraftment and Immune Attack in Solid Tumors

Abstract: Highlights d CD8 + T cell infiltration in tumors is associated with CCL5 and CXCL9 coexpression d CCL5 is expressed in tumor cells and CXCL9 is induced in APCs in response to IFN-g d CCL5 hi CXCL9 hi tumors are immunoreactive and respond to checkpoint blockade d Cancer cells negatively regulate CCL5 expression by epigenetic silencing mechanisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
460
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(534 citation statements)
references
References 67 publications
33
460
1
7
Order By: Relevance
“…Tumor expression of chemokines including CCL5 (Dangaj et al, 2019), CXCL10 (Peng et al, 2015) and the cytokine CSF2 (Borrello et al, 2009) have been linked with the ability of T cells to infiltrate and control tumor growth, and we found that increased mRNA expression of these genes is positively correlated with NFKB2 expression in human melanoma patients (Figure S5A-C). Consistent with a role for non-canonical NF-kB in promoting inflammatory chemokine production, we found increased abundance of RelB at the CXCL10 promoter in BIRC2 KO tumor cells ( Figure 7A).…”
Section: Birc2 Loss Promotes Increased T Cell Migration and Recognitimentioning
confidence: 85%
See 1 more Smart Citation
“…Tumor expression of chemokines including CCL5 (Dangaj et al, 2019), CXCL10 (Peng et al, 2015) and the cytokine CSF2 (Borrello et al, 2009) have been linked with the ability of T cells to infiltrate and control tumor growth, and we found that increased mRNA expression of these genes is positively correlated with NFKB2 expression in human melanoma patients (Figure S5A-C). Consistent with a role for non-canonical NF-kB in promoting inflammatory chemokine production, we found increased abundance of RelB at the CXCL10 promoter in BIRC2 KO tumor cells ( Figure 7A).…”
Section: Birc2 Loss Promotes Increased T Cell Migration and Recognitimentioning
confidence: 85%
“…Consistent with previous reports in the setting of B cell malignancies (Yang et al, 2016), we found that BIRC2 acts as an important negative regulator of the non-canonical NF-kB signaling cascade. Activation of non-canonical NF-kB signaling by genetic deletion of BIRC2 promoted increased tumor cell destruction by upregulating tumor cell antigen presentation pathways and the production of pro-inflammatory chemokines that have been linked with clinical responses to immunotherapy (Dangaj et al, 2019;Harlin et al, 2009;Peng et al, 2015). It is notable that the expression of non-canonical NF-kB transcription factor NFKB2 was positively correlated with survival in patients treated with CTLA blockade (Van Allen et al, 2015) and that NFKB2 and IRF1 expression could predict responses across several clinical cohorts of human immunotherapy patients.…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 and CXCL9 also correlated in this analysis, and dual expression of these chemokines was associated with better prognosis. Interestingly, ovarian cancers with high intra-tumor CD8+ cells but low CCL5 had high levels of CXCL9 transcripts (Dangaj et al, 2019). By contrast, high levels of tumor-associated macrophages, particularly M2-like macrophages, and MDSCs correlate with poor outcome (Drakes and Stiff, 2018;Ruffell and Coussens, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, high levels of tumor-associated macrophages, particularly M2-like macrophages, and MDSCs correlate with poor outcome (Drakes and Stiff, 2018;Ruffell and Coussens, 2015). Aside from describing greater T cell infiltration and better prognosis in BRCA-mutant tumors (Clarke et al, 2009;Rodriguez et al, 2018;Strickland et al, 2016) and examining the regulatory mechanism of specific immune regulatory molecules (e.g., silencing of CCL5 transcription) (Dangaj et al, 2019), these studies are tumor genotype-agnostic. Yet the three mouse models that we examine in detail display major differences in TME, as well as significant differences in chemokine and cytokine gene expression, including tumors where CXCL10 likely directs T cell influx, and others in which T cell influx is associated with Cxcl9.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from our group and others have shown that the chemotactic cytokine CCL5 is widely overexpressed in malignant lesions, directs infiltration of T cells and indicates better prognosis of patients with different types of tumors. [12][13][14][15] As the most important receptor for CCL5, CCR5 is indispensable for the site-specific localization of immune cells. NK cells are also recruited by CCL5 via CCR5.…”
Section: Introductionmentioning
confidence: 99%